Effects of fucoidan supplementation on inflammatory and immune response after high-intensity exercise - Bridget A. McFadden; Caroline S. Vincenty; Alexa J. Chandler; Harry P. Cintineo; Blaine S. Lints; Gianna F. Mastrofini; Shawn M. Arent (Taylor & Francis Group, 2023)
Introduction High-intensity exercise (HIE) can damage the musculotendon complex and impact the immune response, resulting in post-exercise inflammation. Sufficient rest and recovery will improve muscular resilience against future damaging bouts; however, HIE with minimal durations of rest is common in athletic competitions that facilitate persistent inflammation and immune dysregulation. Fucoidans are fucose-rich sulfated polysaccharides with demonstrated anti-inflammatory and pro-immune responses. Fucoidans may improve inflammation and immune responses, which may prove beneficial for individuals who regularly engage in repeated HIE. The research purpose was to investigate the safety and efficacy of fucoidans on inflammatory and immune markers following HIE. Methods Eight male and eight female participants were randomized into a double-blind, placebo-controlled, counterbalanced, crossover design study and supplemented with 1 g/day fucoidan from Undaria pinnatifida (UPF) or placebo (PL) for 2 weeks. Supplementation periods concluded with HIE testing, followed by 1 week of washout. HIE involved one > 30 s Wingate anaerobic test (WAnT) and eight 10 s WAnT intervals. Blood was drawn pre-exercise, immediately post-exercise, 30 min, and 60 min post-exercise to assess immune and inflammatory markers. Blood markers, peak power (PP), and mean power (MP) were analyzed using a 2 (condition) × 4 (time) design. Significance was set at α = .05. Results A time-by-condition interaction was observed for interleukin-6 (p = .01) and interleukin-10 (p = .008). Post hoc analysis revealed greater interleukin-6 and interleukin-10 concentrations at 30 min post HIE with UPF supplementation (p = .002 and p = .005, respectively). No effects of condition were observed for all blood markers or performance outcomes with UPF supplementation (p > .05). Main effects of time were observed for white blood cells, red blood cells, red cell distribution width, mean platelet volume, neutrophils, lymphocytes, monocytes, eosinophils, basophils, natural killer cells, B and T-lymphocytes, CD4 and CD8 cells (p < .05). Discussion No adverse events were reported throughout the study period, indicating a positive safety profile of UPF. While notable changes in biomarkers occurred up to 1 hr post HIE, few differences were observed between supplementation conditions. There did appear to be a modest effect of UPF on inflammatory cytokines potentially warranting further investigation. However, fucoidan supplementation did not influence exercise performance.